2017
DOI: 10.1212/wnl.0000000000003846
|View full text |Cite
|
Sign up to set email alerts
|

Predominantly myalgic phenotype caused by the c.3466G>A p.A1156T mutation in SCN4A gene

Abstract: Objective:To characterize the clinical phenotype in patients with p.A1156T sodium channel mutation.Methods:Twenty-nine Finnish patients identified with the c.3466G>A p.A1156T mutation in the SCN4A gene were extensively examined. In a subsequent study, 63 patients with similar myalgic phenotype and with negative results in myotonic dystrophy type 2 genetic screening (DM2-neg group) and 93 patients diagnosed with fibromyalgia were screened for the mutation. Functional consequences of the p.A1156T mutation were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…There is evidence that EMG abnormalities in patients with myalgia can differentiate an underlying channelopathy from nonspecific myalgic syndromes . In our patients with the p.A1156T mutation, initial EMG studies showed either myotonic discharges or increased insertional activity, as described previously …”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…There is evidence that EMG abnormalities in patients with myalgia can differentiate an underlying channelopathy from nonspecific myalgic syndromes . In our patients with the p.A1156T mutation, initial EMG studies showed either myotonic discharges or increased insertional activity, as described previously …”
Section: Discussionsupporting
confidence: 77%
“…Most SCN4A mutations cause gain‐of‐function defects, either disrupted inactivation or enhanced activation . Mildly attenuated fast inactivation by the p.A1156T channel, demonstrated by functional studies, does not cause clinical myotonia or paramyotonia, although myotonic discharges have been detected by electromyography (EMG) in most such patients . Pain has been reported in various proportions of myotonia patients with different SCN4A mutations …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infants with SCN4A-related myotonia can appear outwardly healthy but present acutely with recurrent episodes of generalized stiffening of the trunk and limbs, apnea, and cyanosis (due to respiratory and laryngeal muscle myotonia-causing laryngospasm) which may be accompanied by bradycardia and loss of consciousness. [13][14][15] We hypothesize that SCN4A mutation may contribute to apnea during the physiological stress of seizures. An erroneous diagnosis of generalized epilepsy is frequently made in these infants.…”
Section: Introductionmentioning
confidence: 99%